Sirtuins functions in central nervous system cells under neurological disorders - Yan, Jing; Tang, Xiaole; Zhou, Zhi-qiang; Zhang, Jie; Zhao, Yilin; Li, Shiyong; Luo, Ailin (Frontiers in Physiology, 2022)
The sirtuins (SIRTs), a class of NAD+ -dependent deacylases, contain seven SIRT family members in mammals, from SIRT1 to SIRT7. Extensive studies have revealed that SIRT proteins regulate virous cell functions. Central nervous system (CNS) decline resulted in progressive cognitive impairment, social and physical abilities dysfunction. Therefore, it is of vital importance to have a better understanding of potential target to promote homeostasis of CNS. SIRTs have merged as the underlying regulating factors of the process of neurological disorders. In this review, we profile multiple functions of SIRT proteins in different cells during brain function and under CNS injury.